2009
DOI: 10.1111/j.1468-3083.2008.02858.x
|View full text |Cite
|
Sign up to set email alerts
|

Lack of association between the promoter polymorphisms at positions –238 and –308 of the tumour necrosis factor alpha gene and acne vulgaris in Polish patients

Abstract: References1 Jensen P, Hansen S, Moller B. Skin cancer in kidney and heart transplant recipients and different long-term immunosuppressive therapy regimens. References 1 Xu SX, Wang HL, Sun LD et al. The familial risk of acne vulgaris in Chinese Hans -a case-control study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 7 publications
1
32
3
Order By: Relevance
“…The Polish and our own studies also investigated the role of the TNFA -238GϾA SNP and acne; no association was reported in either population, suggesting that it might not play a role in the pathogenesis of acne [61,62].…”
Section: The Role Of Tnf-␣ In the Predisposition To Acnementioning
confidence: 99%
See 1 more Smart Citation
“…The Polish and our own studies also investigated the role of the TNFA -238GϾA SNP and acne; no association was reported in either population, suggesting that it might not play a role in the pathogenesis of acne [61,62].…”
Section: The Role Of Tnf-␣ In the Predisposition To Acnementioning
confidence: 99%
“…In the third report, Sobjanek et al reported similar results on a Polish population, with no association between their dataset overall and acne. They did not investigate gender-specific differences [62]. The reason for these differences is currently not clear, but it is interesting that the frequency of the A allele exhibits large geographic difference from east to west [60,61].…”
Section: The Role Of Tnf-␣ In the Predisposition To Acnementioning
confidence: 99%
“…Other authors studied the linkage of acne vulgaris with SNPs of TNF encoding for tumour necrosis factor-α (TNF-α) [7,8,9]. TNF-α is one of the most broadly studied pro-inflammatory mediators, and it is thought to be overexpressed in the inflammatory lesions of patients with acne [10].…”
Section: Introductionmentioning
confidence: 99%
“…The TNFa gene is closely linked to various HLA alleles [10], and this fact sometimes makes it difficult to distinguish between the effect of TNFa from that of other closely linked genes of the major histocompatibility complex. Our results, however, are more similar to the ones recently reported by Sobjanek et al [37]. They did not find any association between the TNFa -308G[A and the -238G[A SNPs and acne vulgaris in the studied Polish population.…”
Section: Discussioncontrasting
confidence: 53%
“…We have also compared the observed allele frequencies of the TNF -308G[A SNP with the two other published dataset investigating the association of this polymorphism and acne vulgaris [5,37]. We found that the frequency of the minor allele containing G/A ?…”
Section: Geographic Differences Of the Observed Allele Frequencies Ofmentioning
confidence: 93%